“How have social grants in Zambia been paid and what lessons can be learnt from this?” - Nkhoma, Henry (Graduate School of Development Policy and Practice, 2020)
From the use of manual payment systems in the delivery of social cash transfers, most developing nations nowadays are resorting to electronic payment solutions to improve the timeliness and effective delivery of the social grants amidst programme scale ups. Like most countries in Sub-Saharan Africa, Zambia recently introduced an electronic delivery system through a commercial bank (ZANACO) and within two years, the Zambia Postal Services Corporation (ZAMPOST) was also engaged as an alternative payment solution for the Social Cash Transfer programme. Zambia’s manual system was designed in such a way that it used teachers or other local civil servants to make cash payments as ‘Pay Point Managers’ (PPMs). The system also uses Community Welfare Assistance Committees (CWACs) to help in the identification of eligible beneficiaries and to monitor payments. This manual payment system was assessed to have administrative and operational weaknesses including corruption and insecurity (because of the physical movement of cash from the bank to the pay points), prompting the introduction of electronic payment solutions. The e-payment system was introduced through ZANACO which is partly owned by the Government and partly private. Apart from Lusaka, this channel was slow in scaling up its services to other areas prescribed in the contract with the responsible Ministry, the Ministry of Community Development and Social Services (MCDSS), and was not very convenient for people with disabilities especially the blind and older persons not used to Automated Teller Machines (ATMs) and pre-paid cards. ZAMPOST was subsequently engaged to cover two provinces with the aim of accelerating e-payment services and improving service delivery of the programme. Instead of developing such a system, however, the Post Office opted to operate just like the manual system, but instead of using PPMs, it opted to use its own employees to physically carry cash to pay points and make payments. This system posed several challenges including poor record keeping leading to payment of ineligible beneficiaries and failure to produce reports. Audit reports revealed grave irregularities with this payment method xii and many stakeholders, including donors were concerned about the poor performance of ZAMPOST. As a contribution to scholarship in the improvement of delivery systems in social protection, this dissertation therefore, highlights the advantages and disadvantages of using the manual as well as the electronic delivery systems in the delivery of social grants. Through the analysis of the manual payment system, e-payment system and the use of the Post Office in Zambia, I investigate how delivery systems are identified, designed and how they function. How they impact on beneficiaries as well as their implication on Government policies. I argue for participatory identification and designing of delivery systems of social grants. In addition, I argue that social grants delivery systems are largely influenced by global trends, whereby some countries adopt what others are using without necessarily considering local implications and capacity to sustain; for instance, mimicking electronic systems used in economically sound countries in the quest to improve efficiency and effectiveness in the delivery of social grants. This study sheds light on how Zambia’s social grants have been delivered vis-à-vis structural fundamentals, design and stakeholder engagement.